(3GdQSGdI GdJOejQjI aj GdWQjbI GdSdajI aj JhMjO GdCSeGA hGdUaGJ hGdbOQI GdEdgjIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3GHQGgje Hf eMeO GdVhHGf s)
(3ChdgG (B:s
(3GdMeO ddg fSJYjfg hfSJgOjg hfSJZaQg CeG HYO abO SFdfi ef JYjfJ CLGHJge Cf CcJH dge eVehf eG SeYhg efi ai HYV GdeLGdS ef cdGe ai GdJhMjO hGdUaGJ hGdTQY hGdbOQ s
(3BNQgG (B:s
(3bGd Hf YHGS QVi Gddg YfgeG Jcad Gddg def bQC GdbQBf hYed HeG ajg Cfg dG jVd ai GdOfjG hdG jTbi ai GdBNQI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B261s
Keywords: (3GdJhMjO hGdedd hGdfMds